Willingness to use carsharing apps: an integrated TPB and TAM. (30th July 2019) - Haldar, Piali; Goel, Pooja
The purpose of this study was to investigate Indian commuters' willingness to use carsharing apps. The present study proposed conceptual framework which makes an original contribution in literature of technology adoption by integrating two behavioural theories that is theory of planned behaviour (TPB) and technology acceptance model (TAM) in the context of willingness to use carsharing apps. The current study examined the relationships among perceived ease of use (PEOU), perceived usefulness (PU), subjective norms (SN), perceived behavioural control (PBC), attitude, and willingness to use carsharing apps. The model was tested empirically by collecting data from 345 respondents. The results exhibited that PU, SN, and attitude had significant positive and PBC had insignificant impact on willingness to use carsharing apps. Further, PEOU was found negatively related to attitude. Overall, the integrated model contributed valuable insights on Indian commuters' willingness to use carsharing apps.